Child marriage in India - Yadav, K. P. (New Delhi, 2006)
Child Marriage is another 'blessing' of the medieval age and it was born from the same compulsions that perpetuated Sati. Child-marriage was not prevalent in ancient India. Svayam-vara can be translated as self selection of one's husband, Svayam-self, Vara-husband. Various types of marriages were prevalant in ancient India Gandharva Vivaha (love marriage), Asura Vivaha (marriage by abduction) etc.
Keywords: Child marriage-India